Identification of Secreted O-Mannosylated Proteins From BCG and Characterization of Immunodominant Antigens BCG_0470 and BCG_0980 - Deng, Guoying; Zhang, Wenli; Ji, Na; Zhai, Yunpeng; Shi, Xiaoxia; Liu, Xin; Yang, Shufeng (Frontiers in Microbiology, 2020)
Bacterial glycoproteins have been investigated as vaccine candidates as well as diagnostic biomarkers. However, they are poorly understood in Mycobacterium bovis strain bacille Calmette-Guérin (BCG), a non-pathogenic model of Mycobacterium tuberculosis. To understand the roles of secreted O-mannosylated glycoproteins in BCG, we conducted a ConA lectin-affinity chromatography and mass spectra analysis to identify O-mannosylated proteins in BCG culture filtrate. Subsequent screening of antigens was performed using polyclonal antibodies obtained from a BCG-immunized mouse, with 15 endogenous O-mannosylated proteins eventually identified. Of these, BCG_0470 and BCG_0980 (PstS3) were revealed as the immunodominant antigens. To examine the protective effects of the antigens, recombinant antigens proteins were first expressed in Mycobacterium smegmatis and Escherichia coli, with the purified proteins then used to boost BCG primed-mice. Overall, the treated mice showed a greater delayed-type hypersensitivity response in vivo, as well as stronger Th1 responses, including higher level of IFN-γ, TNF-α, and specific-IgG. Therefore, mannosylated proteins BCG_0470 and BCG_0980 effectively amplified the immune responses induced by BCG in mice. Together, our results suggest that the oligosaccharide chains containing mannose are the antigenic determinants of glycoproteins, providing key insight for future vaccine optimization and design.